Management of Ebstein’s anomaly - Kron, Irving L.; Roeser, Mark Elliot (Annals of Cardiothoracic Surgery; Vol 6, No 3 (May 31, 2017): Tricuspid Valve Surgery, 2017)
Ebstein malformation is a rare disease that presents with a spectrum of severity. We use a management paradigm that breaks the anomaly into two groups: neonates and children/adults. This leads to a discussion of management and operative techniques as well as pitfalls. We hope the reader finds our streamlined and logical approach of benefit to this complex and rare disease.